Impact of atrazine and nitrate on liver and kidney of egyptian toad Sclerophrys regularis: bioindicator alarming on ecosystem - Mahmoud, Fatma A bdel- Regal (2022)
Atrazine and nitrate have been shown to act as potent oxidative stressors in amphibians either alone or in combination under stable laboratory conditions, causing histopathological alternations in liver and kidney structures at the sub-lethal concentrations. A control group and three treatments groups were tested; atrazine, nitrate, atrazine-nitrate treatments with doses of 300 μg L-1, 200 mg L-1 and their combination respectively. Sever distortion in liver and kidney tissues were shown related to the different treatments. The most hepatic lesions were observed depletion in glycogen content, degeneration of hepatocytes, hemorrhage, necrosis, vasodilatation, congestion in blood vessels, cloudy swelling in the hepatocytes and aggregation of melanomacrophage cells in between the hepatocytes that increased in combination treatment group. In kidney, the most lesions were represented in degeneration of renal tubules, fibrosis, hemorrhage, leucocytes infiltration, thickness in the wall of the renal capsule, atrophy of glomerulus, deformation of Bowman’s epithelium. These negative impacts may be a bioindicator alarming the ecosystem disrupting caused by the uncontrolled apply of these chemicals in agriculture.